Work Engagement di Karyawan: Peran Resiliensi dan Burnout dalam Industri Furnace - Devi Maharani Dwi Arti; Yanto Prasetyo; Hikmah Husniyah Farhanindya (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2026)
Work engagement may be defined as a positive mental state indicating complete involvement in one's professional activities. The objective of this study is to ascertain the relationship between resilience and burnout, on the one hand, and work engagement, on the other, among employees in the head office of a mining services company specialising in furnace, kiln, and demolition services. The present study employed a quantitative approach, utilising a correlational design. A total of 50 students participated in the study by means of a technique known as